Staged transcatheter closure for atrial septal defect and patent ductus arteriosus: a case report. Issue 2 (28th April 2019) - Soma, Yusuke; Shiraishi, Yasuyuki; Kanazawa, Hideaki; Fukuda, Keiichi
Abstract: Background: Atrial septal defect (ASD) and patent ductus arteriosus (PDA) are both common congenital heart diseases, but the combination of these two cardiac defects is extremely rare, and the therapeutic strategy is controversial. Case summary: We treated an adult patient with combined ASD and PDA, and safely attained a successful outcome with two-stage transcatheter closure, which is PDA closure preceding ASD closure, to prevent serious complications. Discussion: Transcatheter closure of one of the defects is now widely accepted as an alternative to surgical closure. In addition, adults with both ASD and PDA are better suited for transcatheter closure than surgical closure. One of the reasons is the difficulty to ligate the ductus arteriosus of an adult patient due to its friability and calcification. Meanwhile, simultaneous combined transcatheter closure of ASD and PDA can result in serious complications, such as thrombocytopenia and haemolysis, whose mechanism is considered to be the destruction of platelets and red blood cells by the residual shunt through implanted devices. Additionally, antiplatelet therapy that prevents device-related thrombus formation after ASD closure can possibly exacerbate thrombocytopenia and haemolysis. Therefore, the staged strategy is reasonable from the perspectives of antiplatelet therapy and haemodynamic changes.